2010
DOI: 10.1021/la104329c
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Assembly of Helical Cyanine Dye Aggregates in the Minor Groove of a DNA Template

Abstract: Double-helical DNA was used as a template for the assembly of helical cyanine dye aggregates. The aggregates consist of cofacial dimers aligned end-to-end in the minor groove of the DNA. The effect of methoxy or fluoro substituents placed on the periphery of the cyanine dye heterocycles on aggregation both in water and on the DNA template was studied by UV-vis and circular dichroism spectroscopy. Methoxy groups were found to be stronger promoters of aggregation than fluoro, and a dimethoxy dye exhibited a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…DZ‐CIS NIR signals were detected at least 7 days after a single administration, like our prototype IR783 and MHI‐148 analogs . DZ‐CIS is prevented from diffusing out from cancer cells by interaction with cellular nucleic acids and proteins …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…DZ‐CIS NIR signals were detected at least 7 days after a single administration, like our prototype IR783 and MHI‐148 analogs . DZ‐CIS is prevented from diffusing out from cancer cells by interaction with cellular nucleic acids and proteins …”
Section: Resultsmentioning
confidence: 87%
“…18,21-23,31 DZ-CIS is prevented from diffusing out from cancer cells by interaction with cellular nucleic acids and proteins. 37,38 After whole body NIR imaging, mice were euthanized at 24 hours and necropsy specimens were again imaged by NIR. Higher NIR signals were detected in xenograft tumors than host tissues (Fig.…”
Section: Dz-cis Accumulates In Burkitt Lymphoma Cells and Tumorsmentioning
confidence: 99%
“…Carbocyanine dyes are bound by proteins and nucleic acids. 6, 7 It is possible that the binding to these macromolecules causes the retention. This unique feature of carbocyanine dye staining will facilitate the noninvasive detection of tumors with a high signal/noise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Inside tumor cells these dyes are bound by proteins or nucleic acids. 6, 7 Binding leads to fluorophore rigidization, causing a marked increase of extinction coefficient favoring NIR detection. 8-10 We previously defined two heptamethine carbocyanine dyes, IR-783 and its synthetic analog MHI-148, that display tumor cell specificity, being taken up and retained by human cancer but not non-cancerous cells due to the differential expression of organic anion transporting peptides (OATPs) in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the addition of substituents can alter the permanent molecular dipole moments and aggregation properties of molecules [25][26][27][28]. Misawa et al measured large changes in the static dipole moments of pseudoisocyanine bromide (PIC-Br) upon J-aggregation, revealing that cyanine molecules had the ability to achieve large static dipole moments [25].…”
Section: Introductionmentioning
confidence: 99%